Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1099/vir.0.80159-0
|View full text |Cite
|
Sign up to set email alerts
|

Bovine enterovirus 2: complete genomic sequence and molecular modelling of a reference strain and a wild-type isolate from endemically infected US cattle

Abstract: Bovine enteroviruses are members of the family Picornaviridae, genus Enterovirus. Whilst little is known about their pathogenic potential, they are apparently endemic in some cattle and cattle environments. Only one of the two current serotypes has been sequenced completely. In this report, the entire genome sequences of bovine enterovirus 2 (BEV-2) strain PS87 and a recent isolate from an endemically infected herd in Maryland, USA (Wye3A) are presented. The recent isolate clearly segregated phylogenetically w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
30
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 24 publications
(28 reference statements)
4
30
0
Order By: Relevance
“…on April 29, 2019 by guest http://aem.asm.org/ significant sequence variation in the 5ЈNCR found among BEV isolates (8,14). This variation is similar to that described for other enteroviruses that exhibit levels of identity between isolates ranging from 70 to 96% (28).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…on April 29, 2019 by guest http://aem.asm.org/ significant sequence variation in the 5ЈNCR found among BEV isolates (8,14). This variation is similar to that described for other enteroviruses that exhibit levels of identity between isolates ranging from 70 to 96% (28).…”
Section: Discussionsupporting
confidence: 50%
“…BEV is very stable in the environment, and thus, it has been proposed that this virus could be a useful indicator of water and environmental contamination (14), as well as a potential surrogate for other highly infectious picornaviruses, such as foot-and-mouth disease virus, in order to optimize extraction and/or detection procedures for contamination of the environment (8,34). The first description of the genetic relationship between simultaneously collected water and fecal samples from a single closed herd showed that in most cases, the sequences detected in water samples were quite similar to those present in feces (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,15,18,19 Because of the unavailability of type specific antisera or a commercially available diagnostic test, a genotypic classification, which supports previous recognized serological distinctions, has been proposed. 7 Despite the large volume of information available on other enteroviruses, very little documentation exists on the pathogenesis of BEV infections in cattle or on its prevalence in North America. Several case reports in the 1950s and 1970s document the isolation of BEV from feces and various tissues from apparently healthy animals or from animals with clinical signs that ranged from mild to moderate diarrhea to reproductive disease.…”
mentioning
confidence: 99%
“…5). 5,7,12 Nucleotide sequence analysis of the 5'UTR and partial VP4 region (nucleotides 1-1000) revealed a 85.5% sequence identity with the UK BEV-1 VG527 strain and 77.8 to 80.7% identity with the Australian BEV-1 isolates, compared to 77.5 to 78% nucleotide identity with the US BEV-2 isolates. Analysis of a much smaller region of the 5'UTR including the 385 nucleotides of the US BEV1-261 isolate (originally isolated in Washington state in 1957) revealed an 87.1% nucleotide sequence identity (data not shown).…”
mentioning
confidence: 99%